Optimizing Canadian Public Immunization Programs: A Prescription for Action - Scheifele, David W.; Naus, Monika; Crowcroft, Natasha S.; Dobson, Simon; Halperin, Scott A.; Bjornson, Gordean (Canadian journal of public health, 2011)
Recent expansion of public vaccination programs for children and youth offers new health benefits but at substantially increased cost. As with other large public investments, immunization programs ought to be systematically evaluated for safety, effectiveness and economic value. At present, program evaluations are suboptimal in most provinces and territories. Experts in public health and vaccinology who attended a workshop in 2009 reviewed the shortcomings and produced "prescriptions for action" to improve matters. Six key recommendations were made: 1) a formal requirement should exist to evaluate all public vaccination programs appropriately; 2) greater voluntary harmonization of programs will facilitate evaluations; 3) a mechanism is needed to prioritize and coordinate program-specific evaluations; 4) new funding mechanisms are needed for basic jurisdictional studies and joint studies of broad relevance; 5) strong emphasis is needed on capacity development and training; and 6) administrative barriers to accessing health information systems and publishing evaluation studies need to be overcome. The expert group considered the need to improve program evaluations as urgent and compelling, with success achievable with dedicated funding and effective leadership. Demonstrating that Canadian immunization programs are among the world's best and safest is a sound strategy for maintaining public participation in those programs. L'expansion récente des programmes publics de vaccination des enfants et des jeunes offre de nouveaux avantages pour la santé, mais à un coût considérablement plus élevé. Comme pour les autres grands investissements publics, il faudrait systématiquement évaluer la sécurité, l'efficacité et la valeur économique des programmes d'immunisation. À l'heure actuelle, les évaluations de programmes sont sous-optimales dans la plupart des provinces et des territoires. En 2009, des experts en santé publique et en vaccinologie qui assistaient à un atelier ont examiné les lacunes de ces programmes et produit des « prescriptions d'action » pour améliorer les choses. Six grandes recommandations ont été formulées : 1) il devrait être formellement exigé d'évaluer convenablement tous les programmes publics de vaccination; 2) une plus grande harmonisation volontaire des programmes facilitera ces évaluations; 3) il faut un mécanisme pour hiérarchiser et coordonner les évaluations de programmes; 4) il faut de nouveaux mécanismes de financement pour mener des études provinciales ou territoriales de base et des études communes présentant un large intérêt; 5) il faut insister vigoureusement sur le renforcement des capacités et la formation; et 6) les obstacles administratifs à l'accès aux systèmes d'information sanitaire et à la publication d'études d'évaluation doivent être surmontés. Le groupe d'experts a considéré qu'il était urgent et incontournable d'améliorer les évaluations de programmes, et qu'on pouvait y parvenir avec un financement particulier et un leadership efficace. Pour soutenir la participation du public, une bonne stratégie consiste à montrer que les programmes d'immunisation canadiens sont parmi les meilleurs et les plus sûrs au monde.